6+4(4x-6)=6-3(2x+1)

Simple and best practice solution for 6+4(4x-6)=6-3(2x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+4(4x-6)=6-3(2x+1) equation:



6+4(4x-6)=6-3(2x+1)
We move all terms to the left:
6+4(4x-6)-(6-3(2x+1))=0
We multiply parentheses
16x-(6-3(2x+1))-24+6=0
We calculate terms in parentheses: -(6-3(2x+1)), so:
6-3(2x+1)
determiningTheFunctionDomain -3(2x+1)+6
We multiply parentheses
-6x-3+6
We add all the numbers together, and all the variables
-6x+3
Back to the equation:
-(-6x+3)
We add all the numbers together, and all the variables
16x-(-6x+3)-18=0
We get rid of parentheses
16x+6x-3-18=0
We add all the numbers together, and all the variables
22x-21=0
We move all terms containing x to the left, all other terms to the right
22x=21
x=21/22
x=21/22

See similar equations:

| x-9/5+9/5=-x/2 | | 0.625(x+10)-10=0 | | 5x/6-1/2=1/3 | | 6*7/12=x | | 1.5•4q-2=4 | | 1.8z+54=1.8 | | x/5+6x=4 | | T(x)=3/2x^2-3x-1 | | 2q+4=-8+8q-6 | | N-3=9-5n | | 13t-7=2 | | w-32=16+2 | | X+3/3+2x+1/12=7/8 | | h/9–12=-4 | | 1/4(2(x-1)+10)=x | | -x+(9/5)x=(7/5) | | w-32=16+ | | m-4×2m=8m | | 3(2x-2)=4(x+1) | | 7=12y | | 3x-5.5=-16.5 | | 1.5•-4q-2=4 | | 22+2/5x-30=16 | | 12x-16=32 | | 1.25m+9=-6 | | 1/4x-8=-7;-4 | | 5(x-2)+30=0 | | 5x/2+x-2/8=2 | | 4/9x-1/4x=11 | | 5(3x-20=20 | | -11x+20=-35 | | x/3-5=100 |

Equations solver categories